Private actor accountability on international regimes - Wahyudi Purnomo; Novita Putri Rudiany; Citra Hennida (Masyarakat, Kebudayaan dan Politik, 2017)
Public-Private Partnerships (PPPs) have emerged along with the growing role of corporations in global development. One of the largest forms of PPP today is the UN Global Compact. The UN Global Compact involves of companies, NGOs, IGOs and state governments. All of them are trying to realize globalization with a more humanist face with attention to the protection of human rights, environment, labor standards and anti-corruption. Engaging private actors in global governance, The UN Global Compact raises many issues such as power, authority, and legitimacy. The effort to tackle it all is to increase PPP accountability. This research seeks to describe what efforts can be made to enhance private accountability within the international regime. The research undertaken is a descriptive study, focuses on public-private partnerships in the UN Global Compact regime. The study found that there were two attempts that could be done. First, by involving the stakeholders in the development of procedures, mechanisms, reporting and monitoring associated with trying to improve the company’s reputation. Second, by looking at corporate relations as agent and UN Global Compact as principal in principal-agent relation in the international regime.